Tuberculosis Risk Stratification of Psoriatic Patients Before Anti-TNF-α Treatment - Benhadou, Farida; Dirix, Violette; Domont, Fanny; Willaert, Fabienne; Van Praet, Anne; Locht, Camille; Mascart, Françoise; Corbière, Véronique (Frontiers in Immunology, 2021)
Psoriasis is a skin inflammatory condition for which significant progress has been made in its management by the use of targeted biological drugs. Detection of latent M. tuberculosis infection (LTBI) is mandatory before starting biotherapy that is associated with reactivation risk. Together with evaluation of TB risk factors and chest radiographs, tuberculin skin tests (TST) and/or blood interferon-γ-release assays (IGRA), like the QuantiFERON (QFT), are usually performed to diagnose M. tuberculosis infection. Using this approach, 14/49 psoriatic patients prospectively included in this study were identified as LTBI (14 TST+, induration size ≥ 10mm), 8 QFT+), and 7/14 received prophylactic anti-TB treatment, the other 7 reporting past-treatment. As the specificity and sensitivity of these tests were challenged, we evaluated the added value of an IGRA in response to a mycobacterial antigen associated with latency, the heparin-binding haemagglutinin (HBHA). All but one TST+ patient had a positive HBHA-IGRA, indicating higher sensitivity than the QFT. The HBHA-IGRA was also positive for 12/35 TST-QFT- patients. Measurement for 15 psoriatic patients (12 with HBHA-IGRA+) of 8 chemokines in addition to IFN-γ revealed a broad array of HBHA-induced chemokines for TST+QFT- and TST-QFT- patients, compared to a more restricted pattern for TST+QFT+ patients. This allowed us to define subgroups within psoriatic patients characterized by different immune responses to M. tuberculosis antigens that may be associated to different risk levels of reactivation of the infection. This approach may help in prioritizing patients who should receive prophylactic anti-TB treatment before starting biotherapies in order to reduce their number.